IMPROVING EMPLOYEE VALUE PROPOSITION IN PT. NMH - Rahayu, Popy; Gustomo, Aurik (Journal of Business and Management, 2017)
Abstract. Background: This research aims to construct driver variables of employee value proposition, on what level each variables has an effect to employee value proposition, and what is the weaknesses of that variable of employee value proposition in PT NMH. Methods: This research used method based on exploratory study then building conceptual model of EVP and create questionnaire design afterward. In collecting the data, questionnaires distributed to 195 employees from 14 divisions in PT. NMH using sampling method. Result: The result of analysis factor Principal Component Analysis found new variables that there are seven variables which effect to employee value proposition, consists of; leadership, company image, communication and working environment, compensation and allowances, opportunity, job, and vision. Based on descriptive analysis found that job has the lowest average score, and the weaknesses of this variable is about Ã¢â‚¬Å“The job as desiredÃ¢â‚¬Â it defined that employees in PT. NMH did not get the job as they wants to get when they choose to work in the company. Conclusion: Based on the result of factor analysis and descriptive analysis that PT. NMH have to concern in Job factors especially in job demands and job resources.Keywords: employee value proposition, driver variable of employee value proposition, PT. NMH